Reimagining Indonesian Language Education in the Digital Age: Integrating Digital Literacy, Critical Thinking, and Cultural Identity - Saharudin Saharudin; Helmi Najamudin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study explores the transformation of Indonesian language education in the digital age by integrating digital literacy, critical thinking, and cultural identity in elementary teacher education. The research was conducted in the Elementary Madrasah Teacher Education Program at Institut Agama Islam Hamzanwadi NW Lombok Timur, Indonesia. In the context of rapid technological development, Indonesian language learning is required not only to develop linguistic competence but also to foster students’ digital literacy and critical thinking skills while maintaining local and national cultural values. This study employs a qualitative descriptive approach using observations, interviews, and document analysis involving lecturers and students in the PGMI program. The findings reveal that the integration of digital platforms, interactive learning media, and collaborative online activities significantly enhances students’ engagement and supports the development of critical and reflective language skills. Moreover, the incorporation of local cultural narratives and Islamic values within digital learning environments strengthens students’ cultural identity and contextual understanding of language use. The study highlights that digital pedagogy in Indonesian language education should not merely focus on technological adoption but must also integrate cultural and ethical dimensions. Therefore, the transformation of Indonesian language learning in teacher education programs is essential to prepare future teachers who are capable of implementing innovative, culturally grounded, and technology-enhanced language instruction in elementary madrasahs